2013
DOI: 10.1002/ange.201305338
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Asymmetric Conjugate Addition of Aldehydes to Nitroolefins: Identification of Catalytic Intermediates and the Stereoselectivity‐Determining Step by ESI‐MS

Abstract: Mit Blick zurück: Die asymmetrische organokatalytische 1,4‐Addition von Aldehyden an Nitroolefine wurde mit ESI‐MS untersucht. Eine Analyse der Rückreaktion ausgehend von quasienantiomeren massenmarkierten 1,4‐Addukten (siehe Schema) lieferte eindeutige Belege für einen Enamin‐ anstelle eines Enol‐Mechanismus und ermöglichte es, den enantioselektivitätsbestimmenden Schritt zu identifizieren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…The Michael addition reaction of cyclohexanone to trans-β-nitrostyrene catalyzed by (1S,4S)-2-tosyl-2,5-diazabicyclo[2.2.1]heptane (2) and (R)-mandelic acid was monitored using high resolution mass spectrometry (MS-TOF), following the methodology previously reported by Wennemers et al [43] From this experiment, it was possible to obtain evidence of the involvement of enamine intermediate I, as well as iminium intermediate II prior to the formation of product III. These observations suggest that the reaction mechanism illustrated in Scheme 2 may be plausible.…”
Section: Resultsmentioning
confidence: 99%
“…The Michael addition reaction of cyclohexanone to trans-β-nitrostyrene catalyzed by (1S,4S)-2-tosyl-2,5-diazabicyclo[2.2.1]heptane (2) and (R)-mandelic acid was monitored using high resolution mass spectrometry (MS-TOF), following the methodology previously reported by Wennemers et al [43] From this experiment, it was possible to obtain evidence of the involvement of enamine intermediate I, as well as iminium intermediate II prior to the formation of product III. These observations suggest that the reaction mechanism illustrated in Scheme 2 may be plausible.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistic studies revealed that the conjugate addition reactions proceed via the formation of an enamine between the peptidic catalyst and the aldehydes and showed that the subsequent C-C bond formation with the nitroolefin is the stereoselectivity-determining and rate-limiting step in the catalytic cycle [31][32][33]. This insight allowed for further optimizing the reaction conditions and reducing the catalyst loading to as little as 0.1%, which is the lowest catalyst loading achieved in enamine catalysis to date [31].…”
Section: Peptide Catalysts With High Chemoselectivity and Reactivitymentioning
confidence: 91%
“…Recently, much efforts has been made to identify novel peptide sequences to promote asymmetric transformations by using combinatorial screenings 7i,8. More precisely, Wennemers has identified the tripeptides H‐Pro‐Pro‐Asp‐NH 2 and H‐Pro‐Pro‐Glu‐NH 2 , respectively, as being efficient for enantioselective aldol reaction and Michael addition by means of an elegant split and mix combinatorial chemistry 7nr,t…”
Section: Methodsmentioning
confidence: 99%